2009
DOI: 10.1071/wf07075
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leaf water content and isoprenoids on flammability of some Mediterranean woody species

Abstract: The impact of water content and isoprenoids on leaf flammability was studied. Field and laboratory experiments were carried out on monoterpene-emitting evergreen broad-leaved species (Quercus ilex, Quercus suber); a needle-leaved species (Pinus halepensis) that emits and stores monoterpenes; an evergreen species (Myrtus communis) that emits isoprene but stores monoterpenes; and a deciduous species (Quercus pubescens) that emits isoprene. Photosynthesis, leaf water content (LWC) and isoprenoid emission were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…This study confirms they have rather short fire intervals due to their high flammability and combustibility but low hazard of reburning, indicating that the fuel rebuilding after a fire is rather slow. On the one hand, P. halepensis in AIXM and P. pinaster forests in MAUR are highly flammable due to a heavy fuel load and high amount of fine particles which burn readily (Ganteaume et al, 2011; see also Dimitrakopoulos et al, 2007;Alessio et al, 2008;De Lillis et al, Author-produced version of the article published in Journal of Environmental Management, 2013, 117, 150-161 Original publication available at http://www.sciencedirect.com/ doi : 10. 1016/j.jenvman.2012.12.006 2009).…”
Section: The Interplay Between Landscape Fuels and Firementioning
confidence: 99%
“…This study confirms they have rather short fire intervals due to their high flammability and combustibility but low hazard of reburning, indicating that the fuel rebuilding after a fire is rather slow. On the one hand, P. halepensis in AIXM and P. pinaster forests in MAUR are highly flammable due to a heavy fuel load and high amount of fine particles which burn readily (Ganteaume et al, 2011; see also Dimitrakopoulos et al, 2007;Alessio et al, 2008;De Lillis et al, Author-produced version of the article published in Journal of Environmental Management, 2013, 117, 150-161 Original publication available at http://www.sciencedirect.com/ doi : 10. 1016/j.jenvman.2012.12.006 2009).…”
Section: The Interplay Between Landscape Fuels and Firementioning
confidence: 99%
“…Previous laboratory-scale studies identified LFF moisture content as a key flammability variable (Pausas et al 2016), as water slows down the heat transmission to the fuel (plant tissues) and interacts with the terpenoids contained in the leaves (Alessio et al 2008b, De Lillis et al 2009). Nonetheless, our results indicated that FMC did not significantly affect the relative importance of terpenoids on sample flammability.…”
Section: Relationship Between Flammability Terpenoids and Fmcmentioning
confidence: 99%
“…Few previous studies focused on the identification of the major terpenoids molecules involved in flammability of vegetation (Owens et al 1998, Ormeño et al 2009, Pausas et al 2016) and investigated the terpenoids-FMC interaction (Alessio et al 2008a, De Lillis et al 2009). During the early steps of this experiment, we tried to correlate the single terpenoids with the measured flammability parameters; we observed that similar molecules belonging to the same terpenoid category produced very different (if not contrasting) effects, without any apparent pattern.…”
Section: Relationship Between Flammability Terpenoids and Fmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is likely that isoprenoids are the fi rst compounds to be ignited and thus could be responsible for the spread of a forest fi re (De Lillis et al 2009 ) . This is mainly related to the emission burst of a considerable amount of these compounds during the fi rst stage of a fi re.…”
mentioning
confidence: 99%